2020
DOI: 10.1063/5.0011957
|View full text |Cite
|
Sign up to set email alerts
|

N 3 + : Full-dimensional ground state potential energy surface, vibrational energy levels, and dynamics

Abstract: The fundamental vibrational frequencies and higher vibrationally excited states for the N3+ ion in its electronic ground state have been determined from quantum bound state calculations on three-dimensional potential energy surfaces (PESs) computed at the coupled-cluster singles and doubles with perturbative triples [CCSD(T)]-F12b/aug-cc-pVTZ-f12 and multireference configuration interaction singles and doubles with quadruples (MRCISD+Q)/aug-cc-pVTZ levels of theory. The vibrational fundamental frequencies are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…They found a slightly larger number of bound states than what was reported by Lee and Secrest earlier. 191 Very recently, Koner et al 192 have computed the bound states of N 3 + in three dimensions, for J = 0, using the TDQMWP method on a newly computed ab initio PES and found that the resulting lowest 20 bound states were in excellent agreement with those obtained using the TIQM method and DVR3D code available. 193…”
Section: Bound States Of Molecular Speciesmentioning
confidence: 81%
“…They found a slightly larger number of bound states than what was reported by Lee and Secrest earlier. 191 Very recently, Koner et al 192 have computed the bound states of N 3 + in three dimensions, for J = 0, using the TDQMWP method on a newly computed ab initio PES and found that the resulting lowest 20 bound states were in excellent agreement with those obtained using the TIQM method and DVR3D code available. 193…”
Section: Bound States Of Molecular Speciesmentioning
confidence: 81%
“…The rovibronic spectrum (X ˜3S À g -A ˜3P u ) analysis provided information about the electronic GS of N 3 + , a linear and centrosymmetric (D Nh ), with an N-N bond length of 1.193 Å. [24][25][26] The GS term of the N 3 + ion is X ˜3S À g , and the first ionization potential (IP) of N 3 with the 2 P g ground state is (11.06 AE 0.01) eV, which was directly measured from the photoelectron spectrum (PES) by A. Morris et al 11 The systems N 3 + (A ˜3P u , 1 1 P u ) and N 3 (X ˜2P g ) are the type-A…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…The 1 3 A ground state PES, correlating with the 3 Σ − g state in linear geometry and dissociating to N + ( 3 P)+N 2 (X 1 Σ + g ), was already discussed in earlier work. 13 Next up in energy are the 1 A and 1 A states (see left panel in Figure 1), which are degenerate for θ = 0, correlate with the 1 ∆ g state and dissociate to N + ( 1 D)+N 2 (X 1 Σ + g ). Upon bending away from the linear structure the degeneracy is lifted and two states -1 A and 1 A -emerge as is shown in Figure 1 middle and right panels.…”
Section: A the Potential Energy Surfaces Of The Excited Statesmentioning
confidence: 99%
“…However, a full-dimensional PES for the electronic ground state has only become available recently. 13 The construction of high-dimensional PESs is a challenging problem for which machine learning-based approaches like neural networks or kernel-based methods have found wide applicability in recent times. [14][15][16][17] One such method, rooted in the theory of reproducing kernel Hilbert spaces (RKHSs), 18 is suitable for obtaining reliable PESs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation